2021
DOI: 10.1177/20458940211007040
|View full text |Cite
|
Sign up to set email alerts
|

Association of right ventricular dysfunction and pulmonary hypertension with adverse 30‐day outcomes in COVID‐19 patients

Abstract: Background: Cardiac manifestations in COVID-19 are multifactorial and are associated with increased mortality. The clinical utility and prognostic value of echocardiography in COVID-19 inpatients is not clearly defined. We aim to identify echocardiographic parameters that are associated with 30-day clinical outcomes secondary to COVID-19 hospitalization. Methods: This retrospective cohort study was conducted in a large tertiary hospital in New York City during the COVID-19 pandemic. It included 214 adult inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 30 publications
2
34
0
2
Order By: Relevance
“…A total of 350 studies were retrieved from the literature search (146 from MEDLINE and 204 from EMBASE). After the selection process, a total of 29 articles were included in the analysis 14 42 (Fig. S1 in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 350 studies were retrieved from the literature search (146 from MEDLINE and 204 from EMBASE). After the selection process, a total of 29 articles were included in the analysis 14 42 (Fig. S1 in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the baseline characteristics of the studies included in the meta-analysis. 29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary hypertension (PH) is being increasingly reported among patients with COVID-19 [46,66,70,71]. Its development is likely multifactorial and may be related to ventilation perfusion mismatch in the setting of significant hypoxic respiratory failure and acute respiratory distress syndrome, increased pulmonary vascular tone in the setting of inflammatory state, and presence of microthrombi or pulmonary embolism in the lungs [13,27,71,72].…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…COVID-19 pandemic caused by the SARS-CoV-2 virus continues to inflict significant morbidity and mortality around the globe . Recent studies suggest potential pathologic interactions between SARS-CoV-2 infection, RV function, pulmonary vascular damages and PH [76][77][78][79][80][81] . Lungs of some patients dying with COVID-19 demonstrated pulmonary vascular involvement in the form of severe endothelial injury, cell death and thrombosis 77,78,80,82 .…”
Section: Bonus Theme: Ph Rv Function and Covid-19mentioning
confidence: 99%
“… 75 , 81 In fact, PH and RV dysfunction were associated with increased odds for 30-day inpatient mortality in COVID-19 patients. 79 It is postulated that increased RV afterload from acute respiratory distress syndrome and pulmonary thromboembolism, negative inotropic effects of cytokines, and direct angiotensin converting enzyme 2 (ACE2)-mediated cardiac injury from SARS-CoV-2 are potential mechanisms of RV dysfunction in COVID-19. 75 …”
Section: Bonus Theme: Ph Rv Function and Covid-19mentioning
confidence: 99%